The future of cell-instructive biomaterials for tissue regeneration–a perspective from early career clinician-scientists - Rangel, Rodrigo; Swanson, W. Benton; Wu, David T. (Frontiers in Materials, 2024)
Cell-instructive biomaterials are an essential component in tissue engineering and regenerative medicine. In the past three decades since the term "Tissue Engineering" was coined, researchers have made significant progress towards regenerating disease or damage tissues and organs by combining innovations in biomaterials, signaling molecules and cell therapies. However, challenges persist including limitations in properties of cell-instructive biomaterials, lack of advanced manufacturing technologies for precise spatiotemporal control of key players in tissue engineering, and regulatory hurdles in clinical translation and regulatory process. In this perspective article, we briefly review the current state of the field including the evolution in our understanding of the role biomaterial mechanics and scaffolding architecture, development of selfhealing and modular biomaterials, and progress in advanced manufacturing technologies such as 3D bioprinting. In addition, we discuss about how innovation in research technologies including multi-omics and spatial biology, and advanced imaging modalities may pave the way for enhancing our understanding about cell-biomaterial interactions. Finally, we present our perspective as early career clinicians and researchers on the key role and potential impact that clinician-scientists can generate in the development, validation, clinical translation and adoption of the next generation of cell-instructive biomaterials for application in engineering tissues and organs to impact human health.